Hiding in plain sight: two new species of diminutive marsupial (Dasyuridae: Planigale) from the Pilbara, Australia - Umbrello, Linette S.; Cooper, Norah K.; Adams, Mark; Travouillon, Kenny J.; Baker, Andrew M.; Westerman, Mike; Aplin, Ken P. (Zootaxa, 2023)
Many of Australia’s smaller marsupial species have been taxonomically described in just the past 50 years, and the Dasyuridae, a speciose family of carnivores, is known to harbour many cryptic taxa. Evidence from molecular studies is being increasingly utilised to help revise species boundaries and focus taxonomic efforts, and research over the past two decades has identified several undescribed genetic lineages within the dasyurid genus Planigale. Here, we describe two new species, Planigale kendricki sp. nov. (formerly known as ‘Planigale 1’) and P. tealei sp. nov. (formerly known as ‘Planigale sp. Mt Tom Price’). The two new species have broadly overlapping distributions in the Pilbara region of Western Australia. The new species are genetically distinct from each other and from all other members of the genus, at both mitochondrial and nuclear loci, and morphologically, in both external and craniodental characters. The new species are found in regional sympatry within the Pilbara but occupy different habitat types at local scales. This work makes a start at resolving the cryptic diversity within Planigale at a time when small mammals are continuing to decline throughout Australia.